2015
DOI: 10.1126/science.aac9462
|View full text |Cite
|
Sign up to set email alerts
|

Principles of connectivity among morphologically defined cell types in adult neocortex

Abstract: Introduction The intricate microcircuitry of the cerebral cortex is thought to be a critical substrate from which arise the impressive capabilities of the mammalian brain. Until now, our knowledge of the stereotypical connectivity in neocortical microcircuits has been pieced together from individual studies of the connectivity between small numbers of neuronal cell types. Here, we provide unbiased, large-scale profiling of neuronal cell types and connections to reveal the essential building blocks of the corte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

90
1,161
6

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 837 publications
(1,257 citation statements)
references
References 66 publications
90
1,161
6
Order By: Relevance
“…(ii) Severed connections are a well-known limitation of slice recordings, which we discussed explicitly on p. 3 of the supplementary materials (SM) for (2). However, we do not agree that our study is substantially more susceptible to connection loss than previous patching studies, most of which also used 300-to 350-mm slices [we found fewer than half a dozen multipatching studies using 450-to 500-mm slices (3)(4)(5)].…”
contrasting
confidence: 52%
See 2 more Smart Citations
“…(ii) Severed connections are a well-known limitation of slice recordings, which we discussed explicitly on p. 3 of the supplementary materials (SM) for (2). However, we do not agree that our study is substantially more susceptible to connection loss than previous patching studies, most of which also used 300-to 350-mm slices [we found fewer than half a dozen multipatching studies using 450-to 500-mm slices (3)(4)(5)].…”
contrasting
confidence: 52%
“…Pearson correlation between connection probability and the correction factor is 0.02. (C) Original connection probability (p) matrix as shown in (2). (D) Corrected connection probability p/(1 -q) matrix.…”
Section: September 2016 • Vol 353 Issue 6304mentioning
confidence: 99%
See 1 more Smart Citation
“…12 In general, intermediary cell types are observed that seem to defy the classification scheme, whether one uses schemes based on morphology, physiology and molecular markers 13 or on gene expression. 14 Conversely, a recent bigdata study 15 reports that it is sufficient to use 3 simple connectivity motives to come to a definite classification, suggesting that also in cortex it may be more useful to consider broader groupings of cell types instead of clearly separable types.…”
mentioning
confidence: 99%
“…This in turn triggers polysynaptic series of events downstream in the network (Komlósi et al, 2012;Molnár et al, 2008;Szegedi et al, 2016;Szegedi et al, 2017). Such powerful synaptic connections between pyramidal cells and interneurons have not been reported in rodent neocortex (Jiang et al, 2015;Miles and Wong, 1986). These specific features were speculated to represent an evolutionary adaptation to the human brain indicating that they might be important for information processing in the human neocortex (Woodruff and Yuste, 2008).…”
Section: Unique Features Of the Human Neocortexmentioning
confidence: 96%